COMPARATIVE STUDY OF ARSENIC AND CADMIUM COMBINED METAL TOXICITY IN FRESH WATER FISH WITH YAMUNA WATER FISH - ARTI SRIVASTAVA; SOHINI SINGH; TANUALLEN (International Journal of Pharma and Bio Sciences, 2015)
Yamuna River is one of the most important natural water resources essential for survival and growth. Over exploitation of this resource has made it one of the most polluted rivers in the world. Heavy metals such as Arsenic and Cadmium enter the aquatic environment due to rapid industrialization and other anthropogenic activities. High cadmium level definitely harms the fish health, since the arsenic present also tends to bioaccumulate in the fish organs, there are possibilities of alteration in toxicity due to the presence of both these metals together. Hence the objective of present study was designed to compare the toxicity due to two metals present together in Yamuna water on the fish Channa punctatus. Accumulation of metals was significantly higher (p < 0.05) in metals in combination as compared to Yamuna water fish with control while lipid peroxidation was significantly higher in Yamuna water fish. Level of catalase, SOD, GSH and GST were significantly lower in both Yamuna water fish and metal treated fish compared to control.